2021
DOI: 10.3390/cells10082161
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Hypoxia Stemness Control

Abstract: Recently, the research on stemness and multilineage differentiation mechanisms has greatly increased its value due to the potential therapeutic impact of stem cell-based approaches. Stem cells modulate their self-renewing and differentiation capacities in response to endogenous and/or extrinsic factors that can control stem cell fate. One key factor controlling stem cell phenotype is oxygen (O2). Several pieces of evidence demonstrated that the complexity of reproducing O2 physiological tensions and gradients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 252 publications
(280 reference statements)
0
16
0
1
Order By: Relevance
“…Even if several pieces of evidence converge in demonstrating that in vitro parameters can influence stem cell properties [50], the current stem cell expansion protocols are frequently set up without considering the native environmental conditions. An underestimated cultural parameter is the oxygen tension that in the majority of stem cell amplification protocols is maintained at air tension levels because it is forgotten that, instead, the natural niche stem cell environment recognizes physiologically low O2 tension in several districts [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even if several pieces of evidence converge in demonstrating that in vitro parameters can influence stem cell properties [50], the current stem cell expansion protocols are frequently set up without considering the native environmental conditions. An underestimated cultural parameter is the oxygen tension that in the majority of stem cell amplification protocols is maintained at air tension levels because it is forgotten that, instead, the natural niche stem cell environment recognizes physiologically low O2 tension in several districts [28].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent literature demonstrates a positive correlation existing between low O2 environment and stemness retention [28], even if few data have been collected to date on AECs. In this context, previous works have reported that AECs under 20% O2 spontaneously reduce the pluripotent expression genes [10] and go into epithelial-to-mesenchymal transition (EMT) [31,32].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…MSCs in mild hypoxia show lower necrosis and cell injury, higher proliferation and preferential differentiation into osteocytes instead of adipocytes, but their metabolism is slowed down, and migration capability is affected [36]. A hypoxic microenvironment influences specific stem cells in different ways, and studies show ambiguous results but the majority agree that hypoxia plays a key role in maintaining stemness and affects differentiation phenotype [37,38].…”
Section: Requirements For Scaffolds For Tissue Engineering Applicationsmentioning
confidence: 99%